Screening 215 Lentil Genotypes under Salinity Stress During the Seedling Stage in Greenhouse Conditions - Ahmad Nezami; jafar Nabati; Mohammad Kafi; Elahe Boroumand Rezazadeh (پژوهشنامه اصلاح گیاهان زراعی)
Extended abstract Background: Salinity stress is one of the environmental stresses that significantly affects the growth of crops, especially in arid and semi-arid regions. With the expansion of salinity, using saline lands for agricultural production has become a significant challenge. Lentil grows in various climatic conditions; however, this plant is sensitive to saline stress. Using saline-tolerant lentil cultivars can help increase production and efficiency in saline soils due to biological nitrogen fixation. This study aimed to investigate the diversity of salinity tolerance in 215 lentil genotypes and select superior genotypes tolerant to salinity. Methods: This study was conducted in the research greenhouse of the Research Center for Plant Sciences, Ferdowsi University of Mashhad, in 2017. In this experiment, 215 lentil genotypes were studied using a completely randomized design with three replications under hydroponic conditions at 12 dS.m-1 sodium chloride salinity. Salinity stress was applied one week after germination. The irrigation method was closed-circuit trickle irrigation. The nutrient solution was replaced weekly, and the salinity level of the nutrient solution was monitored and adjusted daily. Four weeks after the saline treatment, the following parameters were measured and recorded in the vegetative stage: plant height, the number of branches per plant, plant survival rate, the survival percentage of leaves, the percentage of shed leaves, shoot fresh and dry weights, and sodium and potassium contents of shoot. After conducting the data normality test and homogeneity of variances, the means were compared using the Least Significant Difference (LSD) test at a 5% probability level. Cluster analysis using the Ward method, factor analysis, correlation between traits, and the by-plot were performed on the data. The performed grouping was validated through a multivariate analysis of variance and discriminant function analysis. Additionally, to examine the differences between groups in terms of various traits, the means of the groups were compared for the investigated traits. Results: The evaluation of the frequency distribution of lentil genotypes in survival ranges showed that 12% of the genotypes (25 genotypes) had a survival rate of upper 80%, 15 genotypes of which had a survival rate of 100%. On the other hand, 36% of the genotypes (78 genotypes) had a survival rate of less than 20%, with 39 genotypes showing no survival four weeks after 12 dSm-1 salinity stress. In the range of 100-81% survival, six genotypes were at the podding stage. Plant height decreased with a decrease in the survival percentage due to salinity stress. The highest percentage of remaining leaves and the lowest amount of leaf shedding were observed in the three survival ranges of 100-81%, 80-61%, and 60-41%. With a decrease in the survival percentage from 100-81% to 80-61%, 60-41%, and 20-0%, the dry weight of the plant decreased by 13.5%, 22.7%, 36.6%, and 2.03 times, respectively. The tissue water content only significantly decreased in the survival range of 20-0%, and there was no significant difference in this parameter in the other survival ranges. With a decrease in the survival percentage from 100-81% to 80-61%, 60-41%, and 20-0%, sodium concentrations increased by 36%, 48%, 62%, and 2.8 times, respectively. Based on factor analysis under salinity stress conditions, three factors were selected that altogether accounted for 74.4 % of the total data variance. Factor analysis showed that the first factor explained approximately 45.98 % of the variance, which included the percentage of survival, growth stage, plant height, branches number per plant, shoot fresh and dry weights, relative water content with negative loading, sodium concentration, and sodium to potassium ratio with positive loading. The second factor explained approximately 20.1% of the variance, which included the survival percentage of leaves with a positive loading and the percentage of shed leaves with a negative loading. The third factor accounted for 4.8% of the variance, which included potassium concentration with a positive loading. Cluster analysis results showed that the 215 lentil genotypes were grouped into eight plotted groups. The results of discriminant function analysis showed that 92.6% of genotypes were correctly classified, and the success rate of the discriminant function was 100% in groups six, seven, and eight. Genotypes of the cluster sixth, including MLC25, MLC47, MLC64, and MLC77, had the highest values in all studied traits, including survival percentage and growth stage, plant height, branches number per plant, leaf survival percentage, shoot fresh and dry weights, relative water content, and potassium concentration, while they had the lowest values in the percentage of shed leaves, sodium concentration, and the sodium to potassium ratio. Conclusion: Generally, genotypes MLC25, MLC47, MLC64, and MLC77 had the highest values for all studied traits, including survival percentage, growth stage, plant height, the number of lateral branches, the percentage of remaining leaves, fresh and dry weights of shoot, tissue water content, and potassium concentration, while they had the lowest percentage of leaf shedding, sodium concentration, and the Na/K ratio. Considering the superiority of these genotypes in the studied traits, genotypes belonging to this group can be used to study the superior traits in complementary salinity stress studies.